Utilization of Tere Margareth General Hospital Medan After the Implementation of Zoning Policy and Tiered Referral System of BPJS Kesehatan - Mardelina Mardelina; Ida Yustina; Destanul Aulia (International Journal of Health and Medicine, 2026)
The implementation of the tiered referral system and zoning policy by BPJS Kesehatan aims to ensure equitable access to health services. However, in practice, the utilization of services at Tere Margareth General Hospital (RSU Tere Margareth) in Medan remains suboptimal. This condition is reflected in the continuous decline of the Bed Occupancy Rate (BOR) from 2022 to 2024, as well as the low percentage of referrals from six primary health centers within its designated zoning area compared to other Class C hospitals.This study aims to explore the utilization of RSU Tere Margareth and to identify factors influencing its utilization following the implementation of the BPJS Kesehatan zoning and tiered referral policies. The study employed a qualitative approach using a phenomenological method. A total of 19 informants participated in this research, consisting of referred patients, heads of primary health centers, referral officers, and hospital management staff. Data were collected through in-depth interviews, observation, and documentation. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing, supported by source triangulation. The findings indicate that the utilization of RSU Tere Margareth remains low. Contributing factors include the BPJS Kesehatan referral policy system, patients’ level of knowledge, accessibility, service quality, hospital image and reputation, clinical considerations by referral officers, as well as internal and external hospital conditions. It is recommended that the Medan City Health Office and BPJS Kesehatan Medan conduct periodic evaluations and monitoring to ensure equitable referral distribution among Class C hospitals, thereby promoting more balanced hospital utilization in Medan.